2014
DOI: 10.1186/1476-511x-13-111
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel coronary artery disease, free fatty acids, oxidized LDL and its antibody in myocardial infarction

Abstract: BackgroundFree fatty acids (FFA), oxidized low-density lipoprotein (LDL) and its antibodies, lipid profile markers, which are formed under oxidative stress, play an important role in atherosclerotic disease. Assess the levels of these markers in myocardial infarction patients depending on the extent of coronary artery disease (CAD).MethodsST-elevation MI patients with hemodynamically significant stenoses of ≥75% in one, two, three, or more coronary arteries were examined. The patients were divided into three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 19 publications
1
17
0
2
Order By: Relevance
“…It is considered one of the primary causes of disability and death from cardiovascular disease worldwide, and is a leading health threat in humans (1). AMI remains the primary cause of morbidity and mortality worldwide, with ∼7 million patients diagnosed with AMI each year (2,3). AMI continues to be the primary cause of death in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered one of the primary causes of disability and death from cardiovascular disease worldwide, and is a leading health threat in humans (1). AMI remains the primary cause of morbidity and mortality worldwide, with ∼7 million patients diagnosed with AMI each year (2,3). AMI continues to be the primary cause of death in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clinical cardiovascular studies have shown higher IgM anti-MDA-LDL levels are associated with less atherosclerotic burden and better outcomes. In contrast, studies relating IgG antibodies to CHD have been less conclusive [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that lnc-KDM5D-4 was then implicated in hepatic steatosis which can occur independently of insulin resistance in the liver. Given the role of FFAs in the pathogenesis of CAD 31 33 , these results suggest that lnc-KDM5D-4 may play a role in the hepatic metabolism of lipids – a process of well-known relevance to atherosclerosis. Whether aberrant expression of this lincRNA plays an insignificant role in this context, or if it is a mere consequence of disease pathology remains an open question.…”
Section: Discussionmentioning
confidence: 84%